DE JOVEN κορή A ÓPTIMA γαμετή. LA INFLUENCIA GENÉTICA FEMENINA A LOS OJOS DE PLUTARCO - González Almenara, Gillermina (Myrtia, 2004)
From a young κορή lo the best γαμετή. Feminine genetic influence is one of the necessary requirements in order lo show consideration for marrying with the best wife. Feminine genetic influence is important lo ancient Greek society as mach as wife status, because of Plutarch shows consideration for feminine share in procreation.